Renewable gas targets in Australia: an economic perspective - Hancock, Jim; Abdul Halim, Suraya; Kandulu, John; Lester, Laurence; Wagner, Liam (2023)
This presentation reports the results of an investigation of the introduction of Renewable Gas Target (RGT) mechanisms in Australia. An RGT is a mechanism that seeks to increase the share or absolute amount of renewable gases such as green hydrogen in the gas supply. Green hydrogen and biomethane are the most prospective renewable gases although each has its limitations: uncertainties regarding solutions to technical constraints and the need for production cost reductions for green hydrogen and limited supply for biomethane. The first stream of the study investigates the experience of renewable targets in Australia and overseas, taking into account recent and prospective initiatives in Australia. It reports on stakeholder consultations with gas networks, industrial and small gas consumers, renewable gas producers, government policy makers and regulators. It reports a broad range of perspectives on a renewable gas target and the potential use of green hydrogen in the Australian economy. It then proceeds to a discussion of the economic issues arising in the design of an RGT and puts forward some alternatives that could be looked at by policy makers considering a sector-specific initiative and assesses their advantages and disadvantages. The second stream of work involves computable general equilibrium (CGE) modelling of the economic impacts of alternative configurations of an RGT. The CGE modelling proceeds from an emissions trajectory which is consistent with current government policy and in particular net zero by 2050. Net zero by 2050 cannot occur without substantial offset activity and the model allows for it. It takes a baseline scenario without an RGT and develops a number of scenarios with RGT and compares them against baseline. The outputs of the CGE modelling identify impacts on major economic variables of interest such as GDP, per capita consumption, and gross output and populations for the States and Territories.